Come What May - Pomar, Valter (Pontifícia Universidade Católica de São Paulo, 2016)
From 1990 to 2016 the São Paulo Forum has been one of the principle organizational spaces for the Latin American left. The parties that make up the Forum were directly involved in the changes in the regional political conjuncture that occurred beginning with the election of Hugo Chávez, Nestor Kirchner and Luiz Inácio Lula da Silva. The growth of the left in the region was not accompanied by a strategic debate. This did not prevent the electoral victories of the left, but it weakened the left in the face of the rightwing counteroffensive that began in 2008. Today, we need to insert into this assessment and into the strategy for the construction of socialism in the XXIst century an in-depth debate on XXIst century capitalism.